Multi-criterion evaluation of cultivation systems for sustainable algal biofuel production using analytic hierarchy process and Monte Carlo simulation - Ubando, Aristotle T. (Animo Repository, 2014)
The potential benefits from algal biofuels, such as reduced greenhouse gas emissions, come with natural resource consumption and potentially negative environmental and social impact. A multi-criterion approach based on analytic hierarchy process (AHP) and Monte Carlo simulation is proposed to holistically evaluate the suitable cultivation system for sustainable production of algal biofuels. The multiple criteria identified to evaluate the alternatives are: environmental impact, energy consumption, economic viability, technical considerations, and social acceptability. Sub-criteria are defined from these main criteria to further enhance the evaluation of each cultivation system. A case study using Nannochloropsis sp. is then solved to demonstrate the decision model for the following cultivation systems: open pond, flat-panel photobioreactor, and horizontal tubular photobioreactor. The results show that flat panel photobioreactor is the preferred cultivation system to sustainably produce algal biofuels based on the established multi-criterion evaluation using AHP. © 2014 The Authors. Published by Elsevier Ltd.